Pen Fouling in Finisher Pigs: Changes in the Lying Pattern and Pen Temperature Prior to Fouling - Larsen, Mona Lilian Vestbjerg; Bertelsen, Maja; Pedersen, Lene Juul (Frontiers in Veterinary Science, 2019)
Pen fouling, where the pigs choose to rest in their designated excretion area (the slatted floors) and excrete in their designated resting area (the solid floors), is an undesired behaviour and should be prevented when possible. One strategy to prevent fouling is early detection by means of either animal or environmental measures changing prior to fouling. The aim of the present study was to investigate whether the lying pattern of pigs and the temperature in the pen changed the last 5 days prior to an event of fouling and whether this differed from pens without an event of fouling (controls). Fouling events was recorded at pen level when at least half of the solid floor was wet with excreta and/or urine (day0). Each fouling pen was paired with a control pen that had not been scored as a fouling pen prior to or at least 1 week after the fouling event. Fouling and control pens were either not provided with straw or provided daily with 150 g of straw per pig. Percentage of pigs lying on the solid floor and the slatted floor (36 events) as well as pen temperature above the solid and slatted floor (24 events) was analysed using four linear mixed effects models. The percentage of pigs lying on the solid floor decreased (40-24%; P<0.05) while the number of pigs lying on the slatted floor increased (14-24%; P<0.05) from day-2 to day0 only in the fouling pens, with differences seen between fouling and control pens on the same days (P<0.01). However, these changes and differences was only seen in pens without straw. Also only in pens without straw did pen temperature above the solid floor decrease from day-2 to day0 (18.6-17.6 ℃; P<0.001), with differences seen between fouling and control pens only on day0 (P<0.05). In contrast, pen temperature measured above the slatted floor did not change, independent of whether the pen was provided with straw or not. Thus, in pens not provided with straw, both the lying pattern of pigs and pen temperature above the solid floor have potential as early detectors of pen fouling.